For the most part Serious?: The comic potential of authorial metalepsis from Aristophanes to Lucian - Kuhn-Treichel, Thomas (Mnemosyne <Leiden>, 2023)
Abstract Scholarship has drawn a contrast between modern uses of metalepsis (illogical transgressions of narrative levels), which are frequently assigned comic effects, and their ancient counterparts, which are deemed more serious. This article argues that in the case of authorial metalepsis, a way of expression presenting the narrator as bringing about the effects he describes, the comic potential was already discovered in antiquity. Case studies from Aristophanes, Plato, Horace, Juvenal, Ovid, and Lucian demonstrate how ancient authors use authorial metalepsis to evoke paradoxical scenes of interaction across different levels of representation that support a mocking presentation of other authors.